The origin of neocortical nitric oxide synthase-expressing inhibitory neurons - Jaglin, Xavier H.; Hjerling-Leffler, Jens; Fishell, Gord; Batista-Brito, Renata (Frontiers in Neural Circuits, 2012)
Inhibitory neurons are critical for regulating effective transfer of sensory information and network stability. The precision of inhibitory function likely derives from the existence of a variety of interneuron subtypes. Their specification is largely dependent on the locale of origin of interneuron progenitors. Neocortical and hippocampal inhibitory neurons originate the subpallium, namely in the medial and caudal ganglionic eminences (MGE and CGE), and in the preoptic area (POA). In the hippocampus, neuronal nitric oxide synthase (nNOS)-expressing cells constitute a numerically large GABAergic interneuron population. On the contrary, nNOS-expressing inhibitory neurons constitute the smallest of the known neocortical GABAergic neuronal subtypes. The origins of most neocortical GABAergic neuron subtypes have been thoroughly investigated, however very little is known about the origin of, or the genetic programs underlying the development of nNOS neurons. Here, we show that the vast majority of neocortical nNOS-expressing neurons arise from the MGE rather than the CGE. Regarding their molecular signature, virtually all neocortical nNOS neurons co-express the neuropeptides somatostatin (SST) and neuropeptide Y (NPY), and about half of them express the calcium-binding protein calretenin (CR), they thereby constitute a small cohort of the MGE-derived SST-expressing population of cortical inhibitory neurons. Finally, we show that conditional removal of the transcription factor Sox6 in MGE-derived GABAergic cortical neurons results in an absence of SST and CR expression, as well as reduced expression of nNOS in neocortical nNOS neurons. Based on their respective abundance, origin and molecular signature, our results suggest that neocortical and hippocampal nNOS GABAergic neurons likely subserve different functions and have very different physiological relevance in these two cortical structures.